Cryptocurrency Taxation Frameworks: Comparative Analysis Between the EU, US, and Southeast Asia - Loso Judijanto; Aung Myint; Nandar Hlaing (Journal Markcount Finance, 2025)
The rapid growth of cryptocurrency markets has created unprecedented challenges for tax authorities worldwide, particularly in defining ownership, valuation, and jurisdictional liability for digital assets. Divergent taxation policies among major economies have produced inconsistencies in compliance, enforcement, and fiscal fairness. This study aims to conduct a comparative analysis of cryptocurrency taxation frameworks in the European Union (EU), the United States (US), and Southeast Asia, emphasizing their legal classifications, regulatory mechanisms, and fiscal implications. A qualitative comparative method was employed, combining policy document analysis, case law review, and secondary data synthesis from governmental and institutional reports. The findings reveal that the EU prioritizes harmonization through the Markets in Crypto-Assets (MiCA) regulation, the US applies a capital gains taxation model based on asset categorization, while Southeast Asian countries exhibit fragmented and evolving approaches influenced by institutional maturity. The analysis highlights that effective cryptocurrency taxation depends on transparency, interagency coordination, and digital infrastructure readiness. The study concludes that global policy coherence is essential to prevent tax arbitrage and ensure equitable fiscal governance in the digital economy. These results contribute to the development of a unified conceptual framework for cross-border digital asset taxation.